Adoção e uso de comunicações mediadas por computadores : uma análise sob a ótica integrativa das teorias do comportamento planejado e teoria de usos e gratificações - Martins, João Paulo Capelli (2017)
Understanding witch motives are chosen by consumers for adoption and the use of technologies, especially about computer-mediated communications (CMC), represents a fundamental issue both from the academic and managerial point of view, being the subject of several theoretical and empirical studies. Based on this central question, the present study analyzed two theories of different aspects: The Theory of Planned Behavior (TPB) and the Uses and Gratification Theory (UGT) with a sample of users of digital messages (371 cases). With the use of structural equation modeling procedures, a model was tested integrating these two theoretical currents used to explain the adoption and use of digital communication technologies. The results show an impact of TPB variables as attitude with intention to use an CMC. In addition, it was identified the impact of Perceived Control over the behavior of using digital messages. The UGT constructs have a positive effect on TPB also, throughout the variables Entertainment, Pleasure Perceived and Social Interaction over Attitude. In addition, it was verified in this research that Attitude, when incorporated into the complete structural model, becomes a mediating agent in the relationship between Entertainment/Enjoyment Perceived variables and the Intention to Use communication technologies. Based on the results, contributions to the academic knowledge of consumer behavior, as well limitations and developments for future studies are presented in this work.